2018
DOI: 10.1093/gerona/gly117
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Frailty Index Based on Clinical and Laboratory Measurements: Links Between Frailty and Pro-inflammatory Cytokines Differ in a Sex-Specific Manner

Abstract: A frailty index based on clinical deficit accumulation (FI-Clinical) quantifies frailty in aging mice. We aimed to develop a laboratory test-based murine FI tool (FI-Lab) and to investigate the effects of age and sex on FI-Lab scores, FI-Clinical scores and the combination (FI-Combined), as well as to explore links between frailty and inflammation. Studies used older (17 & 23-months) C57BL/6 mice of both sexes. We developed an FI-Lab (blood pressure, blood chemistry, echocardiography) based on deviation from r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…Several other pro‐inflammatory cytokines (eg, IL‐1β, tumor necrosis factor‐α, and IFN‐γ) are also elevated in these mice, but whether this is simply a result of the absence of IL‐10 in this model is not known. Other work has shown that serum levels of various pro‐inflammatory cytokines (eg, IL‐6, IL‐9, IL‐12p40, and IFN‐γ) are increased in naturally aging mice with high frailty index scores . Thus, there is evidence from preclinical studies that chronic inflammation may play a role in the development of frailty but more work in this area is clearly required.…”
Section: Mechanisms Of Frailty In Animal Modelsmentioning
confidence: 99%
“…Several other pro‐inflammatory cytokines (eg, IL‐1β, tumor necrosis factor‐α, and IFN‐γ) are also elevated in these mice, but whether this is simply a result of the absence of IL‐10 in this model is not known. Other work has shown that serum levels of various pro‐inflammatory cytokines (eg, IL‐6, IL‐9, IL‐12p40, and IFN‐γ) are increased in naturally aging mice with high frailty index scores . Thus, there is evidence from preclinical studies that chronic inflammation may play a role in the development of frailty but more work in this area is clearly required.…”
Section: Mechanisms Of Frailty In Animal Modelsmentioning
confidence: 99%
“…However, these deficits have cellular and molecular origins which may add predictive value at much earlier time points if they can be identified. Frailty indices based on deficits in laboratory measures such as blood tests can detect health deficits before they are clinically apparent in both humans and mice Kane et al 2018). Still, even after the development of such composite clocks, the metrics described here -FI, FRIGHT age, and the AFRAID clock -will serve as rapid, non-invasive means to assess biological age and life expectency, accelerating and augmenting studies to identify interventions that improve healthspan and lifespan.…”
Section: Discussionmentioning
confidence: 96%
“…The frailty index has been recently reverse-translated into an assessment tool for mice which includes 31 non-invasive items across a range of systems (Whitehead et al 2014). The mouse frailty index is strongly associated with chronological age (Whitehead et al 2014;Kane et al 2018), correlated with mortality and other age-related outcomes Rockwood et al 2017), and is sensitive to lifespan-altering interventions (Kane et al 2016). However, the power of the mouse frailty index to model biological age or predict life expectancy for an individual animal has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The deficits affect multiple systems in different ways and, as with multimorbidity, the various components of frailty do not occur at the same time or in the same order in individuals but there is an overall increase in frailty with age in both mice and humans, making this a useful measurement of outcomes. The link between frailty and morbidity is not clear, and there are clear sex differences in humans and mice [17][18][19], with females tending to have higher levels of frailty but morbidity being higher in males.…”
Section: (Ii) Frailtymentioning
confidence: 99%
“…A useful overall assessment of the effects of ageing, in both mice and humans, is the Frailty Index (FI). This is a compilation of measurements that provides an overview of the overall ageing of an individual and is comparable in humans and mice [19,[39][40][41][42][43]. There are a range of FIs that have been developed but it is clear that an increased FI is indicative of an increased risk or morbidity [12,44].…”
Section: (Ii) the Frailty Indexmentioning
confidence: 99%